Analisis Unit Cost Sectio Caesaria dengan Metode Activity Based Costing di Rumah Sakit Bhayangkara Yogyakarta - Tsalisah Damayanti (Universitas Muhammadiyah Yogyakarta, 2017)
This study aims to analyze the unit cost of sectio Caesaria by ABC method, second to analyze the differences between the unit cost calculation of Sectio Caesaria by ABC method with applied cost. Unit cost analysis was conducted at Sectio Caesaria procedure without comorbidities or complications. Data that used in the form of primary data interviews with specialists Obgyn and secondary data financial data and hospitals profiles. The result of the calculation of unit cost of Sectio Caesaria service through Activity Based Costing approach is still lower than INA CBG’s tariff.